Operations now - Finch, Byron J. (McGraw-Hill/Irwin, 2008)
Operations Now introduces operations from a vantage point that encompasses both the entire organization and the broader supply network. The author begins his discussion of operations management by first establishing the goal to which any high quality operation must aspire: the goal of profitability. "Operations Now" presents operations within a context that acknowledges its interactions both within all functional areas of an organization as well as the supply chain network serving it.